2014
DOI: 10.1002/mrm.25169
|View full text |Cite
|
Sign up to set email alerts
|

Slab profile encoding (PEN) for minimizing slab boundary artifact in three‐dimensional diffusion‐weighted multislab acquisition

Abstract: Purpose To propose a method for mitigating slab boundary artifacts in 3D multislab diffusion imaging with no or minimal increases in scan time. Methods The multislab acquisition was treated as parallel imaging acquisition where the slab profiles acted as the traditional receiver sensitivity profiles. All the slabs were then reconstructed simultaneously along the slab direction using Cartesian-based sensitivity encoding (SENSE) reconstruction. The slab profile estimation was performed using either a Bloch sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
48
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 14 publications
(26 reference statements)
0
48
0
Order By: Relevance
“…A downside is that the scan time is increased compared with 2D imaging, by the need to acquire different k z -encodes. To address this, Van et al (2015) have proposed a SENSE-like reconstruction to reconstruct all 3D slabs simultaneously, providing an increase in speed of roughly 25–50%. It is important to note here that 3D multi-slab has a higher SNR per unit time, or SNR efficiency (Engstrom and Skare 2013), but the minimum scan time per volume is higher.…”
Section: Discussionmentioning
confidence: 99%
“…A downside is that the scan time is increased compared with 2D imaging, by the need to acquire different k z -encodes. To address this, Van et al (2015) have proposed a SENSE-like reconstruction to reconstruct all 3D slabs simultaneously, providing an increase in speed of roughly 25–50%. It is important to note here that 3D multi-slab has a higher SNR per unit time, or SNR efficiency (Engstrom and Skare 2013), but the minimum scan time per volume is higher.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown previously that this DWI sequence, with phase-encoding gradients applied along the slice-direction for 3D encoding, has higher SNR efficiency than 2D DWI and is well suitable for high-resolution imaging (Engstrom et al, 2014; Engstrom and Skare, 2013; Frank et al, 2010; Frost et al, 2014; Frost et al, 2013; Van et al, 2014). …”
Section: Methodsmentioning
confidence: 94%
“…Previous studies have shown that the slab thickness should be smaller than 30mm in DWI scans with 1000 s/mm 2 b -value (Engstrom et al, 2014; Engstrom and Skare, 2013; Frost et al, 2013; Van et al, 2014), otherwise the artifacts resulting from through-slab phase variations may not be well suppressed by 2D phase correction. In our study, the slab thickness was set to only 9.4 mm in DWI scans with 800 s/mm 2 b -value, and therefore the through-slab phase variations were insignificant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To reduce banding artifacts when stitching the reconstructed slabs together, slab profiles were normalized before profile encoding (PEN) (Van et al, 2015) was performed using a slab profile derived through the Bloch equations. With a 20% overlap between adjacent slabs, the 18 reconstructed slabs were stitched together to produce 144mm of brain coverage in z.…”
Section: Methodsmentioning
confidence: 99%